2019
DOI: 10.1007/s00299-019-02426-w
|View full text |Cite
|
Sign up to set email alerts
|

The Solanum tuberosum GBSSI gene: a target for assessing gene and base editing in tetraploid potato

Abstract: The StGBSSI gene was successfully and precisely edited in the tetraploid potato using gene and base editing strategies, leading to plants with impaired amylose biosynthesis.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 79 publications
6
80
0
1
Order By: Relevance
“…Taken together and compared to our previous work on genome editing in potato [17], our results show that SaCas9 constitutes an alternative to the classical SpCas9. As previous data showed that SaCas9…”
Section: Crispr-sacas9-mediated Gene Editing Of the Potato Genomesupporting
confidence: 79%
See 3 more Smart Citations
“…Taken together and compared to our previous work on genome editing in potato [17], our results show that SaCas9 constitutes an alternative to the classical SpCas9. As previous data showed that SaCas9…”
Section: Crispr-sacas9-mediated Gene Editing Of the Potato Genomesupporting
confidence: 79%
“…Binary plasmids described above were transferred into Agrobacterium C58pMP90 strain by heat shock. Agrobacterium-mediated stable plant transformation and plant regeneration were performed on explants of the Desiree cultivar, as previously described [17]. Plant tissues were cultured on 50 mg/L kanamycin, and regenerated plants were then transferred to a culture medium containing 50 mg/L kanamycin or tested for the presence of the T-DNA by PCR (S2 Table 1).…”
Section: Agrobacterium-mediated Transformation and Plant Regenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we show for the first time that PPE2 strategy developed for dicot species is able to edit an endogenous gene in the cultivated tetraploid potato. Compared to our previous work on cytosine base editing in potato and Arabidopsis (Bastet et al, 2019;Veillet et al, 2019b;Veillet et al, 2019a;Veillet et al, 2020), the efficiency of our PPE strategy appears to be limited, as already observed for cereals. Once improved, the prime editing technology, by largely expanding the range of targeted base substitutions, could make precision breeding amenable in polyploid and vegetatively propagated crops such as potato.…”
Section: Resultsmentioning
confidence: 66%